The case against Christ a critique of the prosecution of Jesus - Dekle, George R., 1948- (Newcastle upon Tyne, UK : Cambridge Scholars, 2011)
Some two thousand years ago, in a small province of the Roman Empire, an obscure Roman governor ordered the execution of a peasant leader. It went virtually unnoticed at the time. No official report of the event has survived, and we would have no memory
Includes bibliographical references (p. [285]-301) and indexes.
Description based on print version record.
Keywords: Jesus Christ -- Trial; Criminal procedure (Jewish law); Criminal procedure (Roman law); Trials (Blasphemy) -- Jerusalem; Trials (Treason) -- Jerusalem; RELIGION / Christian Theology / Christology; Electronic books